2020
DOI: 10.1080/0309877x.2020.1813263
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s just another thing to think about’: encouraging students’ engagement in extracurricular activities

Abstract: spending 10 years working as a solicitor in private practice, Jill moved into academia.Alongside various Course and Research Leadership roles, she has collaborated with both internal and external partners to develop student employability initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…The results confirm that engagement with more ECAs led to a higher overall self-efficacy comparatively. As reported earlier, the numerous barriers to ECA engagement (Dickinson, Griffiths, and Bredice 2020) could indicate that most students will be unable to engage in more than one ECA. In addition to this, students may feel under pressure to focus solely on their studies when they have a number of competing priorities (Stuart et al 2011;Dickinson, Griffiths, and Bredice 2020) and it could be posited that diverting attention to a broader range of activities would have a negative outcome on their self-efficacy.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The results confirm that engagement with more ECAs led to a higher overall self-efficacy comparatively. As reported earlier, the numerous barriers to ECA engagement (Dickinson, Griffiths, and Bredice 2020) could indicate that most students will be unable to engage in more than one ECA. In addition to this, students may feel under pressure to focus solely on their studies when they have a number of competing priorities (Stuart et al 2011;Dickinson, Griffiths, and Bredice 2020) and it could be posited that diverting attention to a broader range of activities would have a negative outcome on their self-efficacy.…”
Section: Discussionmentioning
confidence: 86%
“…Pinto and Ramalheira (2017) found that, regardless of academic performance, graduates who have engaged in ECAs may be more able to highlight their distinctiveness in the job market. Significant barriers to ECA engagement do persist for a range of students, including caring responsibilities, available time, and cultural expectations (Dickinson, Griffiths, and Bredice 2020). Other studies indicate that students with lower academic confidence may avoid ECA engagement, due to worries about being distracted from their studies (Thompson et al 2013;Harvey et al 2017).…”
Section: Ecas and Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…The fifth recommendation focuses on student empowerment and how universities ought to support students, especially those from minority ethnic backgrounds, to capitalise on the different opportunities afforded by higher education (see Brooms, Clark, and Smith 2018). Existing literature has warned that minority ethnic students are more reluctant to seek available support at university (Wong and Chiu 2019) and less likely to participate in extracurricular activities (Dickinson, Griffiths, and Bredice 2020;Miles and Benn 2016), due to differences in cultural expectations or obligations, which can negatively impact on their degree outcomes (Stuart et al 2011). To maximise the values offered by the breath of available resources and activities, we suggest that universities need to be proactive and reflective to ensure that barriers to these participations are reduced or eliminated through additional support or alternative provisions.…”
Section: Addressing the Ethnicity Degree Awarding Gapmentioning
confidence: 99%